Thoughts on Children's Education from the Perspective of Ibn Hajar Al-Haitami - Rahmat Fajar Al-Qusyairi JNZ (STIT Attaqwa, 2024)
According to Ibn Hajar al-Haitami, the purpose of children's education involves efforts to care, develop, and exploit the potential of students so that they are able to understand kitabulloh, have noble morals, and have the skills to lead an independent life. In order to achieve these educational goals, Ibn Hajar al-Haitami wrote a book that specifically discusses various aspects, including educational objectives, educational flow, educator competencies, children's educational techniques, education costs, and characteristics of children's educational institutions. All these components are analyzed and described in his work entitled Tahrīru al-Maqōl Fī Adābi Wa Ahkāmi Wa Fawā'idu Yahtāju Ilaihā Muˋaddibū al-Aṭfāl. The study focused on six aspects of education discussed in the book, using. Descriptive Content Analysis Method, Types of Literature Research, and Descriptive Qualitative Approach. The main data are obtained from Tahrīru al-Maqōl Fī Adābi Wa Ahkāmi Wa Fawā'idu Yahtāju Ilaihā Muˋaddibū al-Aṭfāl, while the secondary data comes from various books discussing the biography of Ibn Hajar al-Haitami. The research process involves three stages: data collection, data processing, and data reporting. The results showed that the focus of children's educational goals emphasizes the development of material and non-material potential of learners. A religious-conservative approach is used in the flow of children's education, with the dominant educational technique being takzir. The competence of educators that is prioritized includes personal and social dimensions, while education financing can be obtained through salaries, endowments, and grants. Ibn Hajar al-Haitami recommended educational institutions in the form of maktab and madrasa.